Bcl‐2 Antagonists Kill Plasmacytoid Dendritic Cells From Lupus‐Prone Mice and Dampen Interferon‐α Production1. Issue 3 (March 2015) - Zhan, Yifan; Carrington, Emma M.; Ko, Hyun‐Ja; Vikstrom, Ingela B.; Oon, Shereen; Zhang, Jian‐Guo; Vremec, David; Brady, Jamie L.; Bouillet, Philippe; Wu, Li; Huang, David C. S.; Wicks, Ian P.; et al.
<x xml:space="preserve">Abstract</x> Objective Interferon‐α (IFNα)–producing plasmacytoid dendritic cells (PDCs) are implicated in the pathogenesis of systemic lupus erythematosus (SLE). IFNα‐related genes are highlighted among SLE susceptibility alleles and are characteristically expressed in the blood of patients with SLE, while in mouse models of lupus, PDC numbers and IFNα production are increased. This study was undertaken to investigate the effects of inhibitors that selectively target different antiapoptotic molecules on the survival of PDCs. Methods PDC numbers, in vitro survival, and expression of antiapoptotic molecules were evaluated in lupus‐prone (NZB × NZW)F1 (NZB/NZW) mice. The impact of Bcl‐2 antagonists and glucocorticoids on PDCs was evaluated in vitro and in vivo. IFNα production by NZB/NZW mice was evaluated before and after treatment with Bcl‐2 antagonists. Results PDCs, but not lymphoid tissue–resident conventional DCs, largely relied on the antiapoptotic protein Bcl‐2 for survival. The enlarged PDC compartment in NZB/NZW mice was associated with selectively prolonged survival and increased Bcl‐2 transcription. Functionally, this resulted in enhanced production of IFNα. Bcl‐2 inhibitors selectively killed mouse and human PDCs, including PDCs from SLE patients, but not conventional DCs, dampened IFNα production by PDCs, and synergized with glucocorticoids to kill activated PDCs. Conclusion Enhanced PDC survival is a likely contributing factor to enhanced IFNα production by lupus PDCs. Bcl‐2 antagonists potently and selectively kill PDCs and reduce IFNα production. Thus, we believe that they are attractive candidates for treating PDC‐associated diseases.